Diagnosing pancreatic cancer in general practice: a cross-sectional study on associations between suspicion of cancer, urgent referral and time to diagnosis. (2nd January 2022) - Virgilsen, Line F.; Rasmussen, Linda A.; Vedsted, Peter; Jensen, Henry
Abstract: Objective: This study aimed to investigate the first point of contact in patients diagnosed with pancreatic cancer, and to study factors associated with the GP's suspicion of cancer, Cancer Patient Pathway (CPP) referral and long diagnostic interval. Design: Cross-sectional study combining register and survey data. Patients: Patients with incident pancreatic cancer recorded in the Danish National Patient Register (n = 303). Main outcome measures: The patient's first point of symptoms presentation, GP's cancer suspicion, CPP referral and diagnostic interval. Results: General practice was the first point of contact for 85.5% of the population. At the first consultation, cancer was suspected in 32.7% and 22.9% were referred to a CPP. The GPs were more likely to suspect cancer or serious illness in patients aged >70 years (prevalence rate ratio (PRR) 1.34, 95% CI 1.09–1.66) and among patients with high comorbidity (PRR 1.23, 95% CI 1.04–1.47). A CPP referral was less likely among patients with low education. The median diagnostic interval was 39 days (interquartile range: 15–72). When the GP initially did not suspect cancer, the likelihood of longer diagnostic interval increased. Conclusion: The majority of patients with pancreatic cancer began their diagnostic route in general practice. Diagnosing pancreatic cancer swiftly in general practice was challenging; the GP did often not initially suspect cancer or refer to a CPP and several of the patient characteristics were associated with the GPs initial suspicion of cancer or CPP referral. Thus, there may be room for improvements in the diagnostics of pancreatic cancer in general practice. Key points: Patients with pancreatic cancer have a poor prognosis, as pancreatic cancer is often diagnosed in late stage. The majority of patients with pancreatic cancer began their diagnostic process in general practice. General practitioners (GPs) suspected cancer at the first consultation in one out of three patients with pancreatic cancer; more often in older and comorbid patients. The GPs suspicion of cancer was associated with urgent referral and shorter time to diagnosis.